Enhancing drilling mud efficiency and environmental safety with biodegradable materials - Yahya Fadhil, Elaf; Hadi, Farqad (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Using biodegradable chemicals such as potassium sorbate, potassium citrate, and potassium bicarbonate in drilling mud is pivotal for enhancing the rheological mud properties while addressing environmental concerns. Despite their proven success in various industries, their potential in drilling operations remains largely untapped. The presence of potassium ions in these chemicals can consider them as promising alternatives to the traditional shale inhibitors including KCl. In this study, different concentrations (1%-7%) of the selected chemicals were incorporated into the drilling mud, with varying weights (3.5g to 24.5g). These drilling muds were then subjected to different tests encompassing mud density, rheology, filtration volume, and pH. The results indicated that potassium sorbate at 7% concentration notably an increase in mud viscosity with a shear stress reading of 150 at 600 RPM. Conversely, potassium citrate exhibited similar rheological properties to KCl, with a shear stress reading of 50 at the same concentration. The results of Potassium bicarbonate are comparable to the results of KCl. Potassium sorbate significantly enhanced the mud filtration properties at 7% concentration, yielding approximately 5 ml filtrate in 7.5 minutes, while the other chemicals showed minimal impact on filtration volume even at higher concentrations. All materials maintained a pH of around 8 at elevated concentrations. This study underscores the potential of biodegradable materials in optimizing rheological mud properties for efficient and environmentally friendly drilling operations.